TANTANGAN DIAGNOSTIK DAN PENATALAKSANAAN NEUROMYELITIS OPTIC SPECTRUM DISORDER: SEBUAH SERIAL KASUS - Luthffia, Audiza; Asmedi, Ahmad; Harahap , Indra Sari Kusuma; Yudiyanta, Yudiyanta (PERDOSNI, 2025)
Introduction: Neuromyelitis optic spectrum disease (NMOSD) is a rare inflammatory CNS disorder consisting of simultaneous optic neuritis and transverse myelitis. The diagnosis requires combinations of clinical characteristics, serologic testing of Aquaporin-4 (AQP4) antibody, and neuroimaging. Treatment includes steroids, plasma exchanges and immunosuppressants. Despite of treatment, NMOSD can lead to devastating sequelae and complications in unresponsive cases. Case Report: We report three cases of adult women with AQP4-antibody positive NMOSD. First case was referral from regional hospital with bilateral visual loss preceded by tetraparesis with relapse and remitting period since 4 years before admission. Second case was referral from regional hospital with persistent right eye visual loss 3 years before admission with acute left eye visual loss and paraparesis. Third case directly admitted to Dr. Sardjito Hospital with acute unilateral visual loss and tetraparesis. Plain head CT scan was performed in the first two cases with normal result and spinal cord MRI in all patients showed long extensive transverse myelitis. All patients received high dose IV Methylprednisolone with immunosuppressant either azathioprine or mycophenolic acid, and continued with plasma exchange for the first two patients. There was no significant improvement in all patients following therapy. Conclusion: All three cases had manifestations of optic neuritis and transverse myelitis, and two of them was referral from regional hospital. Limited access to AQP4-antibody testing and MRI remains a challenge in NMOSD diagnosis, which can lead to delayed in diagnosis. Clinician should suspect for NMOSD in the presence of optic neuritis and myelitis manifestations.